Shared decision making in Eosinophilic esophagitis: Integrating physician and patient perspectives - Kerry A. Ryan; Kelcie K. Darpel; Joel H. Rubenstein; Evan S. Dellon; Lauren P. Wallner; Raymond De Vries; Joy W. Chang (PLoS ONE, 2026)
Background and objectives Shared decision making (SDM) is a patient-centered approach for conditions where multiple, preference-sensitive treatment options exist and there is no single best choice. Eosinophilic esophagitis (EoE), an increasingly prevalent chronic immune-mediated disease, offers an example of how patients and physicians use SDM to navigate the challenging tradeoffs of weighing pharmacologic and dietary therapies. We aimed to identify communication challenges for SDM in EoE care from physician and patient perspectives and to explore how patient treatment preference archetypes influence SDM. Research Design and methods We conducted a qualitative study with one-on-one, semi-structured interviews with adult patients with EoE and physicians. Patients (n = 35) were recruited from a single academic center (mean age 41 years [(SD 15.2]; 51% male; predominantly White 83%). Physicians included gastroenterologists (n = 9) and allergists (n = 7) from varied practices across Michigan. Interview guides were informed by the Theoretical Domains Framework and iteratively refined. Interview transcripts were coded using both deductive and inductive strategies and analyzed thematically via descriptive content analysis. Results Three central themes emerged: 1) Patients often lack knowledge or have misconceptions about EoE and its treatments, but differed in how and from where they want to gain disease-focused information, 2) Physicians generally supported SDM, but patients varied in how they want to be involved in decisions about their care, and 3) Both patients and physicians wanted accurate and user-friendly informational resources about EoE to support effective communication and SDM. Conclusions Our analysis revealed that patients with EoE have diverse preferences for disease-related learning, decision making, and communication. There is a clear need for accurate, accessible, and personalized information to improve patient-physician understanding and communication, without which SDM and patient-centered care in EoE cannot be achieved. What we learned can be applied to other health conditions where there is clinical equipoise between various effective management options.